Comparison of Hazardous Medical Waste Management in Public and Private Hospitals in Takalar Regency - Nurbestari, Isnaeni; Amansyah, Munawir; Sadarang, Rimawati Aulia Insani (Unihealth Community Research, 2025)
Proper management of B3 (Hazardous and Toxic Materials) medical waste in hospitals is essential to prevent adverse impacts on patients, visitors, and healthcare personnel. This study aims to compare the B3 medical waste management practices between public and private hospitals in Takalar Regency. This research employed a quantitative observational method with a cross-sectional approach. The population comprised all medical waste management officers and cleaning service personnel at the selected hospitals. Sampling was conducted using a non-probability total sampling technique, whereby all members of the population were included as research subjects. Data analysis was performed using the Mann–Whitney U test. The results revealed significant differences in waste segregation (p = 0.013), containment (p = 0.001), temporary storage (p = 0.015), and transportation (p = 0.004) practices between public and private hospitals. Both types of hospitals were found not to conduct training on B3 medical waste management for relevant personnel and failed to provide complete personal protective equipment (PPE), such as boots, aprons, gloves, masks, and goggles, during handling activities. It is recommended that both public and private hospitals ensure the availability of adequate and complete PPE, enforce proper usage among medical waste handlers and cleaning staff, and enhance management practices in accordance with established regulations.